Chemical composition of cynara cardunculus L. var. altilis heads: the impact of harvesting time - Mandim, Filipa (2018)
Cardoon is a multi-purpose crop with several industrial applications, while the heads (capitula) are edible and commonly used in various dishes of the Mediterranean diet. Several reports in the literature study the chemical composition of the various plants parts (leaves, flower stalks, bracts, seeds) aiming to industrial applications of crop bio-waste, whereas for the heads, most of the studies are limited to the chemical composition and bioactive properties at the edible stage. In the present study, cardoon heads were collected at six different maturation stages and their chemical composition was evaluated in order to determine the effect of harvesting stage and examine the potential of alternative uses in the food and nutraceutical industries. Lipidic fraction and the content in fatty acids, tocopherols, organic acids, and free sugars were determined. Lipidic content decreases with the maturation process, while 22 fatty acids were detected in total, with palmitic, oleic, and linoleic acids being those with the highest abundance depending on harvesting time. In particular, immature heads have a higher abundance in saturated fatty acids (SFA), whereas the samples of mature heads were the richest in monounsaturated fatty acids (MUFA). The a-tocopherol was the only isoform detected being present in higher amounts in sample Car B (619 μ g/100 g dw). Oxalic, quinic, malic, citric and fumaric acids were the detected organic acids, and the higher content was observed in sample Car E (15.7 g/100 g dw). The detected sugars were fructose, glucose, sucrose, trehalose and raffinose, while the highest content (7.4 g/100 g dw) was recorded in sample Car C. In conclusion, the maturation stage of cardoon heads influences their chemical composition and harvesting time could be a useful means to increase the quality and the added value of the final product by introducing this material in the food and nutraceutical industries.